Addendum to the Checklist of the helminth parasites of vertebrates in Costa Rica - Rodríguez-Ortíz, Beatriz (2004)
In this work, we present an addendum to the “Checklist of the helminth parasites of vertebrates in Costa Rica” with a parasite-host list as well as a host-parasite list. This addendum updates the available information on this group of parasites in Costa Rica, since very recently a new input has been made to describe the helminth fauna of vertebrates, particularly at the Área de Conservación de Guanacaste. In this paper, we add 33 records, representing 23 species. This raises the number of helminth species described in vertebrates from Costa Rica to 325, represented by 89 species of digeneans, 23 of monogeneans, 63 of cestodes, 13 of acanthocephalans, and 137 of nematodes. In total, 133 species of vertebrates have been studied for helminths in Costa Rica (31 species of fishes, 7 amphibians, 18 reptiles, 40 birds, and 37 mammals). Currently, 67 species (20.6 %) have been recorded as new species from Costa Rica and most of them are endemic to particular regions. The Colección de Helmintos de Costa Rica, housed at the Universidad de Costa Rica (UCR), San José, is the depositary of only 23% of the species recorded so far; however this situation is changing and people recognizes.